The Individual Versus the Community in Times of Health Crisis - Véliz-Burgos, Alex (2020)
There is a reflection on people's behaviour in times of crisis.  In this context, the importance of changing the use of the concept of traditional health to that of well-being as part of the development of a community consciousness and a global gaze of the human being is briefly addressed. The need for a socio-emotional education that promotes people's commitment to their geographical socio-partner environment. It is further concluded that human well-being must be confronted from a multidimensional view, where the different spheres involving human development contribute to promoting community life.